2020
DOI: 10.1101/2020.08.09.232405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATP-responsive biomolecular condensates tune bacterial kinase signaling

Abstract: Maintenance of robust biochemical signaling is essential for oligotrophic bacteria that survive under fluctuating environmental challenges. We report that a polar microdomain in Caulobacter crescentus tunes a critical signaling pathway to nutrient availability using the hydrotrope effect of ATP on an intracellular biomolecular condensate. Sequestration of this signaling pathway within a specialized polar microdomain formed by two interacting membraneless organelles, stimulates the activity of a localized kin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 76 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…At the stalked pole, an integral membrane protein, SpmX, interacts with PopZ and localizes the kinase DivJ, thus generating another asymmetry in the cell(43,44). A recent study by Saurabh and colleagues used in vitro reconstitution in solution and on supported lipid bilayers to show that both PopZ and SpmX form condensates via LLPS(45). Furthermore, after heterologous expression of PopZ and SpmX in E. coli, it was found that diffusion of these proteins within the condensates in living cells could be modulated by changing any parameter that affects protein self-interaction (pH, osmolarity, crowding, etc.).…”
mentioning
confidence: 99%
“…At the stalked pole, an integral membrane protein, SpmX, interacts with PopZ and localizes the kinase DivJ, thus generating another asymmetry in the cell(43,44). A recent study by Saurabh and colleagues used in vitro reconstitution in solution and on supported lipid bilayers to show that both PopZ and SpmX form condensates via LLPS(45). Furthermore, after heterologous expression of PopZ and SpmX in E. coli, it was found that diffusion of these proteins within the condensates in living cells could be modulated by changing any parameter that affects protein self-interaction (pH, osmolarity, crowding, etc.).…”
mentioning
confidence: 99%
“…To determine the role of allostery, we found that a functional PAS sensor transmission motif was required for stimulation by PodJ (Fig. 3 Collectively these three studies suggest strategies that concentrate histidine kinases, such as phase separation, may have a generalizable effect of robustly stimulating low copy histidine kinases 9,10 .…”
Section: Discussionmentioning
confidence: 91%
“…More broadly, phase separation provides an accessible compartmentalization strategy for bacterial kingdom 41 . The three scaffolding proteins, PopZ 8 , SpmX 9 , and PodJ (Fig. 4-5), phase separate as two distinct membraneless organelles at opposite ends of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations